Short-term effects and long-term changes of FUEL—a digital sports nutrition intervention on REDs related symptoms in female athletes - Fahrenholtz, I. L.; Melin, A. K.; Garthe, I.; Wasserfurth, P.; Ivarsson, A.; Hollekim-Strand, S. M.; Koehler, K.; Logue, D.; Madigan, S.; Gräfnings, M.; Torstveit, M. K. (Frontiers in Sports and Active Living, 2023)
Female endurance athletes are at high risk for developing Relative Energy Deficiency in Sport (REDs), resulting in symptoms such as menstrual dysfunction and gastrointestinal (GI) problems. The primary aim of this study was to investigate effects of the FUEL (Food and nUtrition for Endurance athletes—a Learning program) intervention consisting of weekly online lectures combined with individual athlete-centered nutrition counseling every other week for sixteen weeks on REDs related symptoms in female endurance athletes at risk of low energy availability [Low Energy Availability in Females Questionnaire (LEAF-Q) score =8]. Female endurance athletes from Norway (n = 60), Sweden (n = 84), Ireland (n = 17), and Germany (n = 47) were recruited. Fifty athletes with risk of REDs (LEAF-Q score =8) and with low risk of eating disorders [Eating Disorder Examination Questionnaire (EDE-Q) global score <2.5], with no use of hormonal contraceptives and no chronic diseases, were allocated to either the FUEL intervention (n = 32) (FUEL) or a sixteen-week control period (n = 18) (CON). All but one completed FUEL and n = 15 completed CON. While no evidence for difference in change in LEAF-Q total or subscale scores between groups was detected post-intervention (BFincl < 1), the 6- and 12-months follow-up revealed strong evidence for improved LEAF-Q total (BFincl = 123) and menstrual score (BFincl = 840) and weak evidence for improved GI-score (BFincl = 2.3) among FUEL athletes. In addition, differences in change between groups was found for EDE-Q global score post-intervention (BFincl = 1.9). The reduction in EDE-Q score remained at 6- and 12- months follow-up among FUEL athletes. Therefore, the FUEL intervention may improve REDs related symptoms in female endurance athletes.